2013
DOI: 10.1186/1471-2393-13-67
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of labour with a Foley catheter or oral misoprostol at term: the PROBAAT-II study, a multicentre randomised controlled trial

Abstract: BackgroundInduction of labour is a common obstetric procedure. At present, different methods are used for induction of labour in women with an unfavourable cervix. Recently, we showed that in term women with an unfavorable cervix the use of a Foley catheter in comparison with vaginal Prostaglandin E2 gel, results in a comparable vaginal delivery rate. A meta-analysis on the subject indicated lower rates of hyperstimulation, and probably as a sequel fewer cases of postpartum haemorrhage. Misoprostol (PgE1) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…2011_010#B2012219), and by the boards of directors of all participating hospitals. The study protocol can be accessed online . The study was conducted in six tertiary and 23 secondary care hospitals in the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…2011_010#B2012219), and by the boards of directors of all participating hospitals. The study protocol can be accessed online . The study was conducted in six tertiary and 23 secondary care hospitals in the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacological methods include many agents, such as PG (PGE2 or PGE1), progesterone receptor antagonists (mifepristone), oxytocin, and nitric oxide (NO) donors, but the most commonly used are prostaglandins and oxytocin. Misoprostol is a synthetic PGE1 analog and is used frequently, because of low cost and easy preservation (refrigeration is not needed), although it is not licensed for labor induction [6,10,19,39,40]. It achieves cervical softening through disintegration and dissolution of extracellular collagen [41].…”
Section: Introductionmentioning
confidence: 99%
“…9 In short, the trial was a multicenter open-label randomized controlled trial studying women with a viable singleton pregnancy beyond 37 weeks of gestation, scheduled for induction of labor, with an unfavorable cervix (Bishop score < 6) and without a previous cesarean section. The study compared induction of labor with oral misoprostol to Foley catheter.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The study showed that induction with oral misoprostol was comparable to Foley catheter in terms of safety and effectiveness. 9 With a comparable safety and effectiveness profile, women's experiences and preferences will become increasingly important.…”
mentioning
confidence: 99%
See 1 more Smart Citation